Adsorption of Heavy Metals from Aqueous Solution onto Sawdust Activated Carbon - Khalid, Marah W.; Salman, Sami D. (Al-Khwarizmi Engineering Journal, 2019)
In this study, sawdust as a cheap method and abundant raw material was utilized to produce active carbon (SDAC). Physiochemical activation was utilized where potassium hydroxide   used as a chemical activating agent and carbon dioxide was used as a physical activating agent. Taguchi method of experimental design was used to find the optimum conditions of SDAC production. The produced SDAC was characterized using SEM to investigate surface morphology and BET to estimate the specific surface area. SDAC was used in aqueous lead ions adsorption. Adsorption process was modeled statistically and represented by an empirical model. The highest specific surface area of SDAC was 688.3 m2/gm. Langmuir and Freundlich isotherms were used to fit the adsorption process, where equilibrium data was best represented by Langmuir isotherm model.  Pseudo-first order and pseudo-second order equations were used to study adsorption kinetics, lead adsorption on SDAC fitted pseudo- second order more adequately. Best removal efficiency was found to be 99.63% with highest adsorption capacity of 19.92 mg/g.